Gambaran pemeriksaan tubex dan widal pada pasien suspek tifoid di RSUP. H. Adam Malik Medan tahun 2023 - Ginting, Radina Yuni Mahesa; Purba, Sanna Kamisna Royani (Journal of Pharmaceutical and Sciences, 2023)
Typhoid fever is a disease that attacks the human digestive tract, and it is very closely related to environmental sanitation factors. This disease occurs in Asian countries, namely Indonesia. This disease can spread through contaminated food and drink caused by Salmonella enterica serovar typhi (S.Typhi) and is an infectious disease. Typhoid fever is an infectious disease caused by Salmonella typhi bacteria; it occurs through food and drink, which causes disease spread by food and drink; the germs will continue to grow and spread into the intestinal tract; symptoms include prolonged high fever, fatigue, headaches, nausea, and pain. Stomach, and constipation or diarrhoea. Some patients will experience changes to have a rash; severe cases can cause serious complications or even death. Typhoid fever can be seen through the blood. The design used in this research was quantitative descriptive with a cross-sectional approach. To determine Salmonella typhi bacteria in samples of typhoid fever patients at RSUP.H. Adam Malik. Of the 69 respondents who underwent the Tubex examination, 34 (49.3%) and Widal 35 (50.7%).